GorimWeb: Role-Playing Game for Hydric Resources Management on Web Platform - Martins, Vinicius; Farias, Giovani; Fernandes, Marina; Barbosa, Raquel; Gonçalves, Eder; Adamatti, Diana (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2024)
Computational games have been increasingly used not only for entertainment but also for corporate training. Role-playing games are particularly well-suited for training purposes. This study focuses on the implementation and analysis of a web-based role-playing game for hydric resources called GorimWeb. For the implementation, various requirements were defined. These included supporting the game board’s playability, storing and exporting data such as logs and chat, accommodating varying numbers of players, and integrating multi-agent systems. Additionally, the game needed a well-structured user interface, good performance, and reliable web availability. The software architecture of the game was also defined. Validation was conducted through two surveys, one before and one after gameplay. The results allowed us to assess the interfaces and hypotheses using the survey responses and the messages exchanged via chat during the game.